Decolonizing methodologies: research and indigenous peoples - Smith, Linda Tuhiwai (Zed Books, 2021)
''To the colonized, the term 'research' is conflated with European colonialism; the ways in which academic research has been implicated in the throes of imperialism remains a painful memory.This essential volume explores intersections of imperialism and research - specifically, the ways in which imperialism is embedded in disciplines of knowledge and tradition as 'regimes of truth.' Concepts such as 'discovery' and 'claiming' are discussed and an argument presented that the decolonization of research methods will help to reclaim control over indigenous ways of knowing and being.Now in its eagerly awaited third edition, this bestselling book includes a co-written introduction features contributions from indigenous scholars on the book's continued relevance to current research. It also features a chapter with twenty-five indigenous projects and a collection of poetry.''– Site de l'éditeur.
Keywords: approches et analyses; cours; discipline; féminisme autochtone; féminisme décolonial; histoire et politique; militance; méthodologie; méthodologie autochtone; pol4105; premier cycle; pédagogie; sciences humaines; système colonial; systèmes d'oppressions; thématiques; études autochtones